PENYULUHAN PROGRAM POKOK ALAT PERMAINAN EDUKATIF MAHASISWA KKN-PPM UNIVERSITAS PGRI ADI BUANA SURABAYA DI DESA BULANG PRAMBON SIDOARJO - Anggreni, Veni; Munawaro, Siti; Anasukha, Endah Wahyu; Jannah, Miftakhul; Suharwati, Nungky; Putri, Hardiyani Eka; Kurniawan, Indra; Rizkianah, Diah; Harnanik, Harnanik (Jurnal Penamas Adi Buana, 2017)
APE is one of the programs that are of interest and attention of the villagers Bulang. APE program's activities consist of three parts: Play Dough, Finger Painting and Puppet Gloves and Socks. Implementation of the 3 parts of APE division performed separately considering the target of three different divisions.Zainal (2013: 153) observation is a process of observation and recording systematically / sequence, logical, objective and rational about various phenomena that exist, both in the actual situation and in artificial situations to achieve certain goals. The method used observation to determine the level of appreciation of the PKK, teachers and children kindergarten / early childhood Bulang village. APE Program activities held on February 9 to 11, 2017. The target participants in the program are 66 participants. Sources of funds derived from the Student Contribution LPPM and corruption in 2017. Keywords : finger painting, play dough and creativity